POLICY ANALYSIS OF THE IMPLEMENTATION OF THE COMMUNITY ACTIVITIES RESTRICTIONS ENFORCEMENT (CARE) ON SMALL AND MEDIUM ENTERPRISES IN MEDAN CITY - Maryam Batubara; Muhammad Arif; Fathur Rahman (JABE (Journal of Applied Business and Economic), 2022)
Covid 19 destroys the joints of life including the economy. To suppress the spread of the COVID-19 virus, several countries have implemented various policies, including Indonesia. Indonesia implements the policy of The Community Activities Restrictions Enforcement (CARE) which also has an impact on the economy. This study aims to determine the impact of The CARE policies on SMEs and the strategies carried out by SMEs during the implementation of The CARE. This research is descriptive research with a qualitative approach. Methods of data collection are done by interview, observation, and documentation. Interviews were conducted with SME associations, SMEs actors, and SMEs regulators. The data analysis technique was carried out by data reduction, data display, and concluding. The data validity technique is done by triangulation of sources and member check. Based on the results of the study, it is known the impact of The CARE policy on SMEs in the city of Medan, namely decreased sales, decreased supplies of materials, layoffs, increased online transactions, and increased innovation. And the strategies carried out by SMEs in the city of Medan during the CARE period were digital marketing, the use of e-commerce, product and service diversification, product quality improvement, and customer relationship marketing.